Biological control of Spodoptera frugiperda Smith, 1797 (Lepidoptera: Noctuidae) by bacteria - Gomes, Jessé Malveira; Godoy, Maurício Sekiguchi de; Barreto, Raphaela Vasconcelos Gomes; Lira, Alcimar Galdino de; Lima, Alricélia Gomes de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
Corn is one of the most produced and important crops in the world and despite high production not Brazil, its production is still compromised by the action of insect pest, with Spodoptera frugiperda Smith, 1797 pest key. Because of this challenge, the continuous usage of insecticides is done aiming to minimize lost in the crops, however, causing great environmental impacts. One of the viable and promising strategies to this arthropod suppression has been the pest integrated management (PIM), which is based on the use of isolated or consortium of controlling techniques, the biological control being one of the most sustainable tools in an ecological perspective. Therefore, the present study had the goal of evaluating the toxicity of the 358.1 bacterial strain isolated from the oil and the supernatant of the cell free culture on the 3rd instar caterpillars control of S. frugiperda, comparing the death rates and effects on their development to the action of commercial chemical insecticide. The experiment was done with 3rd instar caterpillars with three different dilutions of the 358.1 strain, cell free supernatant and fenpropatrin insecticide. Saline solution as negative control. The experiments with the 358.1 strain didn’t show a significant death rate for S. frugiperda. However, contact with the 358.1 culture and its cell free supernatant resulted in increased larval phase duration. Morphophysiological disorders were observed, such as the appearance of adults with atrophied wings, and it is therefore promising to perform new tests.